3(x-1)=4(-2-x)

Simple and best practice solution for 3(x-1)=4(-2-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-1)=4(-2-x) equation:


Simplifying
3(x + -1) = 4(-2 + -1x)

Reorder the terms:
3(-1 + x) = 4(-2 + -1x)
(-1 * 3 + x * 3) = 4(-2 + -1x)
(-3 + 3x) = 4(-2 + -1x)
-3 + 3x = (-2 * 4 + -1x * 4)
-3 + 3x = (-8 + -4x)

Solving
-3 + 3x = -8 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-3 + 3x + 4x = -8 + -4x + 4x

Combine like terms: 3x + 4x = 7x
-3 + 7x = -8 + -4x + 4x

Combine like terms: -4x + 4x = 0
-3 + 7x = -8 + 0
-3 + 7x = -8

Add '3' to each side of the equation.
-3 + 3 + 7x = -8 + 3

Combine like terms: -3 + 3 = 0
0 + 7x = -8 + 3
7x = -8 + 3

Combine like terms: -8 + 3 = -5
7x = -5

Divide each side by '7'.
x = -0.7142857143

Simplifying
x = -0.7142857143

See similar equations:

| 46=17+c | | 11(10)-7=10x | | 8x(6x+3)=-12 | | 8.25t+8=14.5t+13 | | -16+4x=4(x-4) | | 9x^2+7x-9= | | 96=3x-2(-4x-4) | | 5x-3=2y-6 | | y=-4x^2+55x+1200 | | 4x=-5x-9 | | -110+7x+4x=33 | | 20x+8=8(3x-1) | | 7+4(6m+7)=251 | | X^2-20x+100=1 | | (8/3)^-2 | | 4(x-5)=30 | | 7(-4)-5+3(-4)=6+-4-10 | | 6x+3-2x=2(3-x)+9 | | G+10=-8 | | 1/3=2+7/x-4 | | 4(9m-8)= | | 4y+5x=1 | | 4Yy+5x=1 | | x^2+.04=.4x | | x=1.2+1.2+24 | | -V/6=-24 | | s/49 | | -V/6=24 | | x-27-4x=45 | | 9x-4+10-3x=2x+2 | | 4cos^2x+31cos-8=0 | | 3(2p-7)=3(p+1) |

Equations solver categories